The dose–response relationship between smoking and the risk factor for invasive pulmonary aspergillosis in patients with severe fever with thrombocytopenia syndrome - Dai, Yan; Pu, Qinqin; Hu, Nannan; Zhu, Jin; Han, Yaping; Shi, Ping; Li, Jun; Jin, Ke (Frontiers in Microbiology, 2023)
Objectives Invasive pulmonary aspergillosis (IPA) is common in immuno-compromised people, and a high incidence of IPA has been found in patients with severe fever with thrombocytopenia syndrome (SFTS). Our study aimed to determine the independent risk factors for IPA and the relationship between smoking status and the risk of IPA in SFTS patients. Methods A retrospective analysis of SFTS patients in the First Affiliated Hospital of Nanjing Medical University from May 2011 to December 2021 was reviewed. The patients were divided into two groups: IPA and non-IPA groups. We compared demographic characteristics, clinical manifestation, laboratory parameters, treatment, and prognosis, and explored the risk factors of IPA using logistic regression and ROC curve. The dose-dependent effect of smoking on the risk of IPA was further estimated, including the age of smoking initiation, daily smoking amount, smoking duration, and pack-years of smoking. Results In total, 189 individuals were included. Compared with the non-IPA group, the IPA group had higher levels of smoking, drinking, cough, dyspnea, aCCI scores, Dabie bandavirus (DBV) RNA load, ferritin, PCT, IL-6, APTT, LDH, BUN, creatinine, and lower levels of FT4 and TSH. The incidences of MODS, admission to ICU, ventilation, and broad-spectrum antibiotic treatment were significantly higher in the IPA group than in the non-IPA group. Multivariable logistic analysis showed that smoking history, cough, creatinine, admission to ICU, broad-spectrum, and corticosteroid therapies were the independent risk factors for IPA in SFTS patients. We further confirmed that the age of smoking initiation <30 years, smoking at least one pack per day, smoking for at least 40 years, and having at least 40 pack-years of smoking exposure were the independent risk factors for IPA among smokers. Conclusion The prognosis of SFTS patients in the IPA group is worse than that of the non-IPA group. Attention should be paid to SFTS patients with a smoking history, cough, creatinine, admission to ICU, and broad-spectrum and corticosteroid therapies. There is a strong dose-dependent association between smoking and IPA development in SFTS patients. Prophylactic antifungal therapy should be considered for SFTS patients with these risk factors, but further studies are necessary to determine if it is beneficial for the prognosis of these patients.